Preparation of carbon nanotubes by seeded catalyst method using palm oil as starting material / Isrihetty@Siti Salmah Senain - Senain, Isrihetty@Siti Salmah (2008)
Carbon Nanotubes (CNTs) are produced by Thermal Chemical Vapor Deposition (TCVD). The function of support catalyst is to optimize used of the catalyst. The morphology and crystallinity of CNTs produced are determined by Fourier Transmission Infrared Spectroscopy (FTIR). The catalyst was prepared by the sol-gel method with cobalt, iron and nickel as the catalyst where these catalysts were added with different percent of support catalyst. In the synthesizing of CNTs, the palm oil was used as precursor. The collected CNTs are carried out for characterization by using FTIR. Increasing the percent of support catalyst contributes to the unstableness of carbon bonding of CNTs. The CNTs will vibrate more and absorb more energy. In this study, the energy absorbance of CNTs will be varied depends on the catalyst used.